Gerakan Sehat Bersama Koemang (Kulit Manggis) di Desa Batu Mekar - Rahman Djalun; Adhara Putri Prasanty; Zahra Khoerunnisa; Aminah Swarnawati (Communio: Jurnal Pengabdian Kepada Masyarakat, 2023)
Koemang is a type of herbal medicine that is processed from mangosteen rind which is rich in benefits. Mangosteen rind extracted from selected mangosteen fruit from Batu Mekar village, West Nusa Tenggara province. Koemang is one of the healthy living movement programs that utilize local plant-based food products that we can use as herbal medicines that have various benefits. One of them is maintaining immunity, maintaining immunity, and many more. We from group 8 class H of Development Communication created this movement with the aim of informing and educating how we as Indonesians are healthy by utilizing local fruit products. The implementation method used in service activities consists of planning where in planning activities there is team coordination, timing of activities, and coordination with partners. Furthermore, for the implementation of training and mentoring and ending with an evaluation. The results of the implementation are related to marketing not only with direct marketing but partners need to do online marketing using the simplest way by using social media as a container. Here we use two social media as a forum for campaigning information related to the importance of a healthy lifestyle and providing educational campaigns about how important it is to change a healthy lifestyle by utilizing local products as supporting materials. The social media that we use as a platform for campaigns are Instagram and Facebook as platforms. We can adjust this in relation to the target market we are aiming for as our target.